A review of hydrogen production via biomass gasification and its prospect in Bangladesh - Salam, M.A. (Elsevier Ltd, 2018)
Hydrogen has been using as one of the green fuel along with conventional fossil fuels which has enormous prospect. A new dimension of hydrogen energy technology can reduce the dependency on non-renewable energy sources due to the rapid depletion of fossil fuels. Hydrogen production via Biomass (Municipal solid waste, Agricultural waste and forest residue) gasification is one of the promising and economic technologies. The study highlights the hydrogen production potential from biomass through gasification technology and review the parameters effect of hydrogen production such as temperature, pressure, biomass and agent ratio, equivalence ratios, bed material, gasifying agents and catalysts effect. The study also covers the all associated steps of hydrogen separation and purification, WGS reaction, cleaning and drying, membrane separation and pressure swing adsorption (PSA). To meet the huge and rising energy demand, many countries made a multidimensional power development plan by adding different renewable, nuclear and fossil fuel sources. A large amount of biomass (total biomass production in Bangladesh is 47.71 million ton coal equivalent where 37.16, 3.49 and 7.04 MTCE are agricultural, MSW and forest residue based biomass respectively by 2016) is produced from daily uses by a big number of populations in a country. It also includes total feature of biomass gasification plant in Bangladesh. Â© 2018 Hydrogen Energy Publications LLC